2014
DOI: 10.1007/s00382-014-2141-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Pacific Decadal Oscillation on the summer precipitation over East China: a comparison of observations to 600-years control run of Bergen Climate Model

Abstract: Observations show that the summer precipitation over East China often goes through decadal variations of opposite sign over North

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…An overall oscillation in regional mean ET 0 is found in China, which was not revealed by the previous studies, suggesting that the variation of ET 0 from 1961 to 2011 should be a phenomenon of earth’s atmospheric circulation. PDO is considered as the important earth’s climatic driving power for the continental hydro-meteorology abnormality such as shift of dry/wet in Asia, especially in China30313233. The PDO driven climate oscillations impart clear influences to the regional ET 0 in China as a whole, indicated by significant negative correlation between annual PDO index and annual mean ET 0 ( r  = −0.384; p  < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…An overall oscillation in regional mean ET 0 is found in China, which was not revealed by the previous studies, suggesting that the variation of ET 0 from 1961 to 2011 should be a phenomenon of earth’s atmospheric circulation. PDO is considered as the important earth’s climatic driving power for the continental hydro-meteorology abnormality such as shift of dry/wet in Asia, especially in China30313233. The PDO driven climate oscillations impart clear influences to the regional ET 0 in China as a whole, indicated by significant negative correlation between annual PDO index and annual mean ET 0 ( r  = −0.384; p  < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The successful simulation of the rainfall decadal shift is based on the successful simulation of the three-dimensional spatial structure of the decadal variation of EASM circulation. Several factors are responsible for the decadal variation of EASM and the associated rainfall, including the decadal modulation of EI Niño-Southern Oscillation (ENSO)25, Tropical Indian Ocean warming4, PDO phase transition12, SST variation in the Atlantic26, etc. It shall be noted that these signals are all from the ocean, and some of them can be regarded as the internal variability of the climate system.…”
Section: Resultsmentioning
confidence: 99%
“…AMIP-type numerical experiments implied that the recent warming over the tropical oceans, especially those associated with the PDO centered over the central and eastern Pacific, has played a major role in the weakening of the EASM during recent decades10. Numerical experiments further demonstrated that the shift of PDO from positive to negative phase probably induces warming of the Lake Baikal and the weakening of the westerly jet through the air-sea interaction in the Pacific, changing the summer precipitation pattern in East China1112. Some studies argue that, apart from PDO, Atlantic multi-decadal oscillation (AMO) can also modulate the decadal variation of the EASM through the air-sea coupled processes in the Indian Ocean and North Pacific13.…”
mentioning
confidence: 93%
“…Yu et al (2015) recently pointed out that the existence of warm winter sea surface temperatures during positive PDO phases in the eastern subtropical Pacific would propagate to the tropics in the following summer due to the weakening of the oceanic meridional circulation and the existence of a coupled wind-evaporation-SST feedback mechanism, and would thus result in a warming in the eastern tropical Pacific Ocean in summer. As a consequence, these events would lead to increased summer precipitation over the Yangtze River and decreased precipitation over North China.…”
Section: Discussionmentioning
confidence: 99%